P22 Application of the recent bts guidelines to a population of nodule patients. (15th November 2016) - Morgan, AJ; Rosewarne, D; Bapusamy, A; Tanner, K; Hancock, J; Reid, D; Mathews, S
Abstract : The BTS nodule guidelines utilise morphological features, volume measurement, and risk modelling to stratify nodule management- potentially time consuming methods which may be offset by the possibility of early discharge Our aim was to identify patients who may be suitable for immediate (volume <80mm 3 or 5mm) or early discharge (stable interval volumetry or VDT >800 days) from our previous Flesichner driven follow-up, and to estimate reduction in future CTs –'scans saved', by noting the number of CTs that would have remained in their original schedule. 118 patients were identified. 22 patients had nodules <5 mm, discharge would save 28 future scans. Of 12 patients with 5–5.9mm nodules, 6 patients were dischargeable (4 volume <80 mm 3, 2 benign morphology), saving 10 future CT scans. For patients with larger nodules and CT scans at least a year apart, serial volumetry identified 17 patients with nodules 6–7.9mm of which 15 were either morphologically benign, <80 mm 3, static in volume or VDT >800 days, and thus dischargeable saving 15 future CT scans; and 9 patients with >8 mm nodules of which static volumetry was noted in 6, saving 8 future scans. All patients with a CT follow up period of between 3 months and 1 year (n = 44) had static linear measurements and volumetry was not retrospectively performed on these. Total discharges were 51 (see table), with a saving of 61 scans compared to historical protocol. Discharge of patients with nodules < 5 mm is a one off gain as these will not enter follow up in the future. Excluding these, results in an ongoing saving of 33 scans if 34 patients undergo either paired or one off volume measurements, taking an average of 5 minutes to perform. Additional volumetry at 3 months would add a further 5minutes to analysis of these patients CTs. We believe the 'trade off' between time for volumetry versus reduced CTs (radiology time, radiation exposure and patient inconvenience) is favourable and should provide an incentive for units to offer volume measurements, performed as in this study by either chest radiologist or trained chest physician, if they are not already doing so.